Catch composition, Effort, and Selectivity of Fishes of Recreational Fishing in YucatAn, Mexico (Global Journal of Science Frontier Research, 2018)
Fishing for recreational purposes is a component rarely studied. This activity represents a potential competition with artisanal fisheries, although its impact on fish stocks remains unknown in many coastal areas worldwide. Here, In this study we described the catch composition, the catch per unit effort (CPUE), size at first capture (L 50 ) and the length-weight relationship (LWR) of the fish species caught by the recreational fishing from the coastal area off Chuburna Puerto, Yucatan, Mexico. During an annual cycle a total of 1,241 specimens of 21 fish species, belonging to 13 families, were collected with hook and line, as the main fishing gear used by the recreational fishing in the region. The species Haemulon plumieri and Sphoeroides nephelus were captured all along the study period and contributed with 43.07% and 30.55% of the total biomass, respectively. Seven species are known to have a commercial interest for exploitation and 10 with minor commercial interest.
Keywords: recreational fishing; catch composition; catch per unit effort; length-weight relationship; Haemulon plumieri; Sphoeroides nephelus; yucatan